THE EFFECT OF PLASTIC DEFORMATION ON WEAR RESISTANCE OF AUSTENITIC MANGANESE STEEL ASTM A-128 GRADE C - Taufiqurrahman Fattah, Zufar
Austenitic manganese steel is known as very good wear resistance steel. Wear resistance is the fundamental characteristic of material performance, especially for engineering applications with surfaces in contact with each other. In this research, wear resistance was determined by using pin on disk equipment and using austenitic manganese steel as the specimen. The test was carried out with the same load and rotational speed and cold rolling reduction as variations for the specimen. In addition, the surface conditions specimen before and after the wear test were also observed. Wear resistance is shown as a function of mass loss. The higher mass loss of specimen, the lower the wear resistance of the specimen. From the test, it was found that the as-cast manganese steel ASTM A- 128 grade C specimens had higher wear resistance than the as-heat treated spcimens through the two step heating method. Furthermore, the strain reduction range of 5%-10% from cold rolling resulted in the most optimum level of wear resistance for austenitic manganese steel.